ANALISIS PENGEMBANGAN KARIR KARYAWAN PADA PT. XYZ KOTA MAKASSAR - Badaruddin Badaruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
Research executed as a mean to analyse the factors influencing career development applied individually by employees of at PT. XYZ Makassar. Result of research indicate that the internal factor and eksternal of individual career covering the existence of career planning, individual career development activity, performance and interest, related/relevant organizational policy of career, tuition and support of part of officer, and also organizational head support give the very influence of signifikan statistically to individual career development effort. Model the linear equation prove that 63,0% change strive the individual career development of employees of because of existence of variation of internal factor variable change and individual eksternal career, and also 37,0% because of other;dissimilar factor outside analysis of penelitian.Variabel of performance and interest of at internal factor of career and also variable of tuition and support of part of officer statistically more dominant influence the individual career development effort at employees PT. XYZ Makassar